Treatment and outcomes of acute basilar artery occlusion in the Basilar Artery International Cooperation Study (BASICS): a prospective registry study - Schonewille, Wouter J.; Wijman, Christine AC; Michel, Patrik; Rueckert, Christina M; Weimar, Christian; Mattle, Heinrich P; Engelter, Stefan T; Tanne, David; Muir, Keith W; Molina, Carlos A; Thijs, Vincent; Audebert, Heinrich; et al. (The lancet, 2009)
Background - Treatment strategies for acute basilar artery occlusion (BAO) are based on case series and data that have been extrapolated from stroke intervention trials in other cerebrovascular territories, and information on the efficacy of different treatments in unselected patients with BAO is scarce. We therefore assessed outcomes and differences in treatment response after BAO. - Methods - The Basilar Artery International Cooperation Study (BASICS) is a prospective, observational registry of consecutive patients who presented with an acute symptomatic and radiologically confirmed BAO between November 1, 2002, and October 1, 2007. Stroke severity at time of treatment was dichotomised as severe (coma, locked-in state, or tetraplegia) or mild to moderate (any deficit that was less than severe). Outcome was assessed at 1 month. Poor outcome was defined as a modified Rankin scale score of 4 or 5, or death. Patients were divided into three groups according to the treatment they received: antithrombotic treatment only (AT), which comprised antiplatelet drugs or systemic anticoagulation; primary intravenous thrombolysis (IVT), including subsequent intra-arterial thrombolysis; or intra-arterial therapy (IAT), which comprised thrombolysis, mechanical thrombectomy, stenting, or a combination of these approaches. Risk ratios (RR) for treatment effects were adjusted for age, the severity of neurological deficits at the time of treatment, time to treatment, prodromal minor stroke, location of the occlusion, and diabetes. - Findings - 619 patients were entered in the registry. 27 patients were excluded from the analyses because they did not receive AT, IVT, or IAT, and all had a poor outcome. Of the 592 patients who were analysed, 183 were treated with only AT, 121 with IVT, and 288 with IAT. Overall, 402 (68%) of the analysed patients had a poor outcome. No statistically significant superiority was found for any treatment strategy. Compared with outcome after AT, patients with a mild-to-moderate deficit (n=245) had about the same risk of poor outcome after IVT (adjusted RR 0·94, 95% CI 0·60-1·45) or after IAT (adjusted RR 1·29, 0·97-1·72) but had a worse outcome after IAT compared with IVT (adjusted RR 1·49, 1·00-2·23). Compared with AT, patients with a severe deficit (n=347) had a lower risk of poor outcome after IVT (adjusted RR 0·88, 0·76-1·01) or IAT (adjusted RR 0·94, 0·86-1·02), whereas outcomes were similar after treatment with IAT or IVT (adjusted RR 1·06, 0·91-1·22). - Interpretation - Most patients in the BASICS registry received IAT. Our results do not support unequivocal superiority of IAT over IVT, and the efficacy of IAT versus IVT in patients with an acute BAO needs to be assessed in a randomised controlled trial. - Funding - Department of Neurology, University Medical Center Utrecht.
Gesehen am 17.03.2021